Evaluation of Microstructural and Mechanical Properties of Ag-Diffused Bulk MgB2 Superconductors - Yilmazlar, M.; Terzioglu, C.; Dogruer, M.; Karaboga, F.; Soylu, N.; Zalaoglu, Y.; Yildirim, G.; Ozturk, O. (Springer Science and Business Media LLC, 2013)
Electrical, microstructural, and mechanical properties of undiffused and Ag-diffused bulk MgB2 superconductors are systematically studied using dc resistivity, scanning electron microscopy (SEM), and Vickers microhardness (H V ) measurements. The resistivity (at room temperature), critical (onset and offset) temperature, variation of transition temperature, hole-carrier concentration, surface morphology, Vickers microhardness, elastic modulus, and yield strength values of the samples are obtained and compared with each other. One can see that all superconducting parameters given above depend on the Ag diffusion on MgB2 system. The obtained results illustrate that the room temperature resistivity reduces with the increment of diffusion annealing temperature because of the hole filling when the onset ( $T_{c}^{\mathrm{onset}}$ ) and offset ( $T_{c}^{\mathrm{offset}}$ ) critical temperatures determined from the resistivity curves are obtained to enhance from 38.4 to 39.7 K and from 36.9 to 38.8 K, respectively. Further, SEM studies carried out for the microstructural characterization demonstrate that the surface morphology and grain connectivity also improve with the increase of the diffusion annealing temperature. In fact, the best surface morphology is observed for the Ag-diffused bulk MgB2 superconductor exposed to 850 °C annealing temperature. Besides, it is obtained that the load-dependent microhardness values reduce nonlinearly as the applied load increases until 2 N, beyond which the curves shift to the saturation region, presenting that all the samples exhibit the indentation size effect (ISE) behavior. Further, the elastic modulus and yield strength values observed decrease with the enhancement of the applied load.
Keywords: Ag diffused MgB2; Transition temperature; Scanning electron microscopy; Vickers microhardness; Transition Temperature; Ag diffused MgB2; Scanning Electron Microscopy; Vickers Microhardness; 2. Zero hunger